Some Unanticipated Consequences of Organizational Restructuring - McKinley, William; Scherer, Andreas Georg (Academy of Management Review, 2000)
We explore two consequences of organizational restructuring that are unanticipated by managers. At the cognitive level of analysis, we propose that organizational restructuring has the unanticipated consequence of producing cognitive order for top executives, and at the environmental level, organizational restructuring has the unanticipated consequence of contributing to long-term environmental turbulence. Both feed back to promote further organizational restructuring, making restructuring a self-reinforcing loop. We derive formal propositions from this theoretical framework, discuss issues in testing the propositions, and specify implications for future theory building and management practice.